Effects of Antioxidant Vitamins (C,E, Beta-Carotene) Supplementation of Cardiovascular Biomarkers Among Males with Risk Factors in Boushehr, Iran - Boushehri, Saeid Najafpour (2011)
Iran, as an Eastern Mediterranean country,has accepted the western lifestyle with respect to nutrition habits, physical inactivity and smoking which contribute to higher prevalence of cardiovascular disease (CVD) risk factors among the Iranian community. In recent years (2006)CVD is the first cause of death in Iran with 167.7 deaths per 100,000 people, 23.4% wasted age (the years which person lives with disability) and 37% of all deaths were due to CVD.Two hundred (200) male subjects with age ≥40 years old were recruited in single-blinded, randomized intervention study at Persian Gulf Health Research Center, Bushehr University of Medical Sciences.The objective of this study was to determine biomarkers risk of CVD, measured at baseline and subsequently after 12 weeks of supplementation with vitamin E (400 IU), C (500 mg), beta-carotene (15 mg), and combined (E, C, and betacarotene) supplements and placebo, respectively. Socio-economic indices, dietary intake, anthropometry, biochemical indices, were collected. As for biochemical test studied include fasting blood sugar (FBS), lipid profile: total triglycerides (TG), total cholesterol (TC), low density lipoprotein cholesterol (LDL-C), high density lipoprotein cholesterol (HDL-C), antioxidant vitamins (E, C, and beta-carotene) and inflammatory factors: high sensitive C-reactive protein (hs CRP), 8-iso-prostaglandin F2α, enzymatic oxidative defense: glutathione peroxidase (Gpx), superoxide dismutase (SOD), and also oxidized LDL (oxLDL), and total homocysteine (tHcy) were measured.The mean age of the subjects was 52.85±7.96 years old and the mean BMI was 27.56±4.26 kg/m2. In C group, dietary scores were for cereal 94.7, bread 93.1, beef 73.4. In E group, cereal had dietary score of 95.2, followed by bread 93.4.In beta-carotene group, cereal had dietary scores of 96.2, bread 90.8, dates 85.2. In combined group, dietary scores for cereal were 96.2, bread 94.2 and dates 85.9. In placebo group, rice received scores of 95.2, followed by bread 92.2.Among the subjects, 12.3 % had high fasting blood sugar (FBS) level and 80.1 % were normal level. Those subjects that had hypercholesterolemia and hypertriglyceridemia were 19.9 % and 41.4 % respectively. This study also showed that 13.3 % of the total subjects had high level of LDL-C and 6.6 % with lower level of HDL-C. Result also indicated that 8-iso-PGF2α significantly decreased in groups E 17.62 % (p=.000), beta-carotene 17.56 % (p=.002), and combined 14.97 % (p=.014). For hs-CRP was significantly decreased in groups C 28.14 % (p=.036), E 23.27 % (p=.020), beta-carotene 27.93 (p=.021), and combined 23.69 (p=.0005). The oxidized LDL was significantly decreased in groups C 18.32 % (p=.005), E 23.86 % (p=.000), beta-carotene 17.31 % (p=.000), and combined 19.07 %(p=.000). However, SOD was found to have significantly increased in groups C 26.76 % (p=.0003), and combined 35.77% (p=.000). Whereas for Gpx, result also shown to have significantly increased in groups E 7.13 % (p=.003), and combined 5.34 % (p=.017)before and after the intervention. In conclusion, the findings from this study demonstrated that supplementation of antioxidant vitamins improved some of enzymatic antioxidant systems included SOD and Gpx, and decreased harmful biomarkers for cardiovascular diseases included hs-CRP, oxLDL, and 8-iso-PGF2α.People at risk for heart disease should be encouraged to use supplementation of antioxidant vitamins to reduce the occurance of cardiovascular diseases.